Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa melalui Metode Penemuan Terbimbing - Naomi Teti Ngedi1; Samuel Igo Leton; Aloysius Joakim Fernandez (Asimtot : Jurnal Kependidikan Matematika, 2019)
This research aims to know the effect of guided discovery method in increasing the students’ mathematical problem solving ability. The type of the research is quantitative with pre experimental design. The experiment used was one group pretest-posttest design. The samples were taken from class VIID which consisted of 30 students, randomly selected from 5 existed classes. The type of the data of this research was premier data. The data collection was done by using tests, each consisted of 5 analysis questions. The technique of analyzing data was t-test showed that and at a significant level 5% which means that . Therefore, H0 was refused and Ha was accepted. Hence, a conclusion could be drawn that there was a significant effect in using guided discovery method in increasing the students’ mathematical problem solving ability.